REKAYASA PERANGKAT LUNAK PENGARSIPAN DIGITAL DOKUMEN ACCOUNTING FINANCIAL DENGAN PENDEKAN METODE MVC - Nasri, Edy; Hendra, Yul; Farezi, M Nur (Jurnal Ilmiah Sains dan Teknologi, 2021)
In the activities of document interception has an important role in the processing of document archiving in an agency or company and is used in supporting administrative processes or other activities. If the archiving of documents owned is not well managed can lead to difficulty finding the information that has been stored and ultimately can hinder the next stage of the work process. In the practice of paper-based records management, many problems are faced, thus giving space to electronic media as an alternative in archiving management. In archival terminology, electronic media is grouped as a new media archive, one form of storage of new media archives is digital media. Digital media usually requires tools in the form of computers, because it cannot be read directly, can be processed in computer programs and stored in digital data storage media. In This research discussed how to design, implement the system and maintenance and security of documents so as to avoid damage. This Software Engineering was created with MVC approach by using Framwork Codeigniter with the aim of archiving this digital document done to help and prevent a very long process in the storage and search of a document needed in a fast, precise and detailed time